Gereja dalam Menghadapi Tantangan Sosial, Politik, dan Budaya dari Abad Ke Abad - Iman Pasrah Zai; Malik Bambangan (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
Throughout history, the church has faced various social, political, and cultural challenges that have continued to evolve over time. The church has functioned not only as a religious institution but also as an agent of change actively responding to social dynamics. In its early days, the church struggled to maintain its existence amid political persecution by the Roman Empire, followed by a process of adaptation when Christianity became the official religion. During the Middle Ages, the church responded to cultural transformations such as the Renaissance and played a significant role in education and intellectual development, although it often clashed with emerging new ideas. In the Reformation era, the church faced an internal crisis that led to major changes in doctrine and religious practices.